Right Diaphragmatic Peak Motion Velocities on Pulsed Wave Tissue Doppler Imaging in Neonates: Method, Reproducibility, and Reference Values. (21st February 2019) - Maurizio, Radicioni; Rinaldi, Victoria Elisa; Camerini, Pier Giorgio; Salvatori, Cristina; Leonardi, Alberto; Bini, Vittorio
Abstract : Objectives: To test the reproducibility and report the reference ranges of the right diaphragmatic excursion's peak velocities recorded by pulsed wave tissue Doppler imaging in healthy term neonates. Methods: We formerly assessed intraobserver and interobserver variability of the method for the right hemidiaphragm in a small group of neonates, including ventilated neonates. We did not attempt to test the approach for the left hemidiaphragm because of the recognized high failure rate of visualization. Next, we recorded the peak velocities of both hemidiaphragms throughout inspiration and expiration in 229 healthy term neonates near birth to establish weight‐dependent reference ranges for the measurements. Results: The study population included 116 male and 113 female neonates. The reproducibility of the technique was excellent even in neonates supported by ventilation. We always recorded the right diaphragmatic peak velocities in the normative study group, whereas the left ones were only recorded in 110 of 229 (48%) and 148 of 229 (65%) neonates from the anterior and lateral views, respectively. The modality of delivery and sex showed no influence on diaphragmatic kinetics. The mean inspiratory peak velocities ± SD were 1.4 ± 0.2 cm/s for the right hemidiaphragm and 1.5 ± 0.3 cm/s for the left hemidiaphragm. The mean expiratory peak velocities were 1.3 ± 0.2 cm/s for the right hemidiaphragm and 1.4 ± 0.3 cm/s for the left hemidiaphragm. Conclusions: Measurement of right diaphragmatic kinetics as assessed by pulsed wave tissue Doppler imaging was found to be a reliable technique. Its clinical applicability for the prompt diagnosis and effective management of neonatal respiratory failure deserves further investigation.